2022
DOI: 10.1017/s0033291722001428
|View full text |Cite
|
Sign up to set email alerts
|

Do antidepressants prevent transition to psychosis in individuals at clinical high-risk (CHR-P)? Systematic review and meta-analysis

Abstract: Background Emerging meta-analytical evidence indicates that baseline exposure to antipsychotics in individuals at clinical high-risk for psychosis (CHR-P) is associated with a higher risk of an imminent transition to psychosis. Despite their tolerability profile and potential beneficial effects, baseline exposure to antidepressants (AD) in CHR-P has surprisingly received far less attention as a potential risk modulator for transition to psychosis. The current systematic review and meta-analysis were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 88 publications
1
12
1
Order By: Relevance
“…These challenges are common in psychotherapy trials . The very low adherence to fluoxetine (26.8%) led to insufficient power, though its timing (6 months postbaseline) may have been too delayed to protect against transition to psychosis . Despite the moderate fidelity to CBCM, findings indicate that the greater the change in cognitive biases or vulnerabilities, the greater the clinical improvement across both treatment groups, suggesting the psychological target of CBCM may represent more of an outcome rather than mediating variable.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…These challenges are common in psychotherapy trials . The very low adherence to fluoxetine (26.8%) led to insufficient power, though its timing (6 months postbaseline) may have been too delayed to protect against transition to psychosis . Despite the moderate fidelity to CBCM, findings indicate that the greater the change in cognitive biases or vulnerabilities, the greater the clinical improvement across both treatment groups, suggesting the psychological target of CBCM may represent more of an outcome rather than mediating variable.…”
Section: Discussionmentioning
confidence: 70%
“…The current study (Staged Treatment in Early Psychosis [STEP]) aimed to evaluate the outcomes of a sequential multiple assignment randomized clinical trial (SMART) comprising support and problem solving (SPS), cognitive-behavioral case management (CBCM), and fluoxetine for individuals at ultrahigh risk for psychosis . These treatments and their sequence were selected due to their potential benefits and safety profile . The sequential treatment strategy, which examined the efficacy of escalating the intensity and duration of treatment for individuals who did not remit on a randomized basis, was expected to produce superior outcomes over 12 months than single-phase trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, APs administration was associated with an increased risk of imminent conversion to psychosis; a possible explanation is that APs prescription may be a “red flag,” an indicator of a greater baseline severity that needs to be carefully monitored ( 112 ). Moreover, recent meta-analytical evidence with CHR-P individuals ( 113 ) displayed that being already exposed to antidepressants (ADs) treatment at intake was associated with a lower conversion rate to psychosis at follow-up. In discussing this result, it is relevant to consider that conversion to psychosis is based entirely on the progression of positive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analytical evidence on CHR-P cohorts revealed that baseline exposure to antipsychotics or antidepressants has a tangible modulating effect on the longitudinal risk of transition to a first-episode of psychosis. Indeed, baseline exposure to antipsychotics is associated with a higher risk of transition to psychosis in comparison to antipsychotic-naïve individuals (29% v. 16%, risk ratio (RR) 1.47) (Raballo, Poletti, & Preti, 2020b), whereas baseline exposure to antidepressant is associated with a lower risk of transition to psychosis in comparison to antidepressant-naïve individuals (13.5% v. 21%, RR 0.71) (Raballo, Poletti, & Preti, 2023).…”
Section: Introductionmentioning
confidence: 99%